Respuesta :
m∠EFG = 3n + 23
m∠GFH = 4n + 17
m∠EFG + m∠GFH = 180
(3n + 23) + (4n + 17) = 180
(3n + 4n) + (23 + 17) = 180
7n + 40 = 180
- 40 - 40
7n = 140
7 7
n = 20
m∠EFG = 3n + 23
m∠EFG = 3(20) + 23
m∠EFG = 60 + 23
m∠EFG = 83
m∠GFH = 4n + 17
m∠GFH = 4(20) + 17
m∠GFH = 80 + 17
m∠GFH = 97
m∠GFH = 4n + 17
m∠EFG + m∠GFH = 180
(3n + 23) + (4n + 17) = 180
(3n + 4n) + (23 + 17) = 180
7n + 40 = 180
- 40 - 40
7n = 140
7 7
n = 20
m∠EFG = 3n + 23
m∠EFG = 3(20) + 23
m∠EFG = 60 + 23
m∠EFG = 83
m∠GFH = 4n + 17
m∠GFH = 4(20) + 17
m∠GFH = 80 + 17
m∠GFH = 97
Answer: m∠EFG=83°
m∠GFH =97°
Step-by-step explanation:
Given : ∠EFG and ∠GFH are a linear pair.
m∠EFG=3n+23, and m∠GFH=4n+17.
We know that linear pair of angles added up to 180 degrees.
i.e [tex]\angle{EFG}+\angle{GFH}=180^{\circ}[/tex]
[tex]\Rightarrow\ 3n+23+4n+17=180\\\\\Rightarrow\ 7n+40=180\\\\\Rightarrow\ 7n=180-40\\\\\Rightarrow\ 7n=140\\\\\Rightarrow\ n=\dfrac{140}{7}=20[/tex]
Now, m∠EFG=(3n+23)°= (3(20)+23)°=(60+23)°=83°
m∠GFH =(4n+17)°=(4(20)+17)°=(80+17)°=97°